2001
DOI: 10.1152/jappl.2001.90.4.1227
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of PGE2and COX-2 production in rabbit uterine cervical fibroblasts

Abstract: Prostaglandins (PGs) cause uterine contraction to initiate labor at term. We investigated the effect of progesterone and 17beta-estradiol on the production of PGE2 in rabbit uterine cervical fibroblasts. When the cervical fibroblasts were treated with interleukin-1alpha (IL-1alpha), the level of PGE2 was augmented in a time- and dose-dependent manner. The IL-1alpha-augmented PGE2 level was almost completely suppressed by progesterone and 17beta-estradiol at the physiological concentration (0.01 microM), wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…This observation has also been reported in microglia (52) and uterine fibroblasts (42). Whether COX-2 and PGE 2 are essential to the expression in the cerebral endothelium of cell adhesion molecules and whether this process is regulated by 17␤-estradiol remains to be elucidated.…”
Section: Discussionsupporting
confidence: 69%
“…This observation has also been reported in microglia (52) and uterine fibroblasts (42). Whether COX-2 and PGE 2 are essential to the expression in the cerebral endothelium of cell adhesion molecules and whether this process is regulated by 17␤-estradiol remains to be elucidated.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, PGE 2 production in the reproductive tract was also down-regulated by progesterone; we recently reported that in rabbit uterine cervical cells, progesterone inhibits the PGE 2 production via the inhibition of COX-2, but not COX-1 production. 34) Very similar regulation by steroid hormones of prostaglandin G/H synthase-2 has been observed in bovine myometrium. 35) In contrast, there have been few reports that describe the effects of antiprogesterone on connective-tissue metabolism; mifepristone suppresses the production of metalloproteinase inhibitors in cultured human and rat granulosa cells.…”
Section: Discussionmentioning
confidence: 58%
“…The steady-state level of COX-1 mRNA was unaffected by the administration of estrogen as well. In these findings, the hOB cells are distinguished from various cell models of human and animal origin that exhibited increased expression of COX-1 or COX-2 following estrogen exposure [47,48,49].The site of estrogen modulation of hOB cell PGE 2 biosynthesis was not determined by the present studies. The observation that PGE 2 production was elevated in estrogen-pretreated samples stimulated by TGFβ and TNF is firmly established, as is the observation that 17β-E 2 treatment did not limit hOB cell PGE 2 biosynthesis.…”
mentioning
confidence: 50%
“…The steady-state level of COX-1 mRNA was unaffected by the administration of estrogen as well. In these findings, the hOB cells are distinguished from various cell models of human and animal origin that exhibited increased expression of COX-1 or COX-2 following estrogen exposure [47,48,49].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 98%